2018
DOI: 10.1080/02701367.2018.1441485
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Aerobic Training Successfully Improves Lipid Profile of Dyslipidemic Women: A Randomized Controlled Trial

Abstract: Water-based interval aerobic training positively affected the lipid profile in premenopausal dyslipidemic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…Our analysis of five studies 23 , 24 , 27 , 34 , 38 revealed a significant ( P < 0.001) moderate effect size point estimate of 0.610 in favour of AHIIT compared with the control for peak oxygen uptake (VO 2 peak) (95% CI 0.277 to 0.943), with no significant heterogeneity found (I 2 = 26.69%, P = 0.244) ( Fig. 2 a).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Our analysis of five studies 23 , 24 , 27 , 34 , 38 revealed a significant ( P < 0.001) moderate effect size point estimate of 0.610 in favour of AHIIT compared with the control for peak oxygen uptake (VO 2 peak) (95% CI 0.277 to 0.943), with no significant heterogeneity found (I 2 = 26.69%, P = 0.244) ( Fig. 2 a).…”
Section: Resultsmentioning
confidence: 83%
“…2 e). Although our analysis of two studies 27 , 31 indicated that both blood lipid measurement regarding HDL and LDL had insignificant (P = 0.273) and small (P = 0.327) effect size point estimates of 0.240 (95% CI -0.189 to 0.669) and −0.285 (95% CI -0.853 to 0.284), respectively, there was no significant heterogeneity across studies: (I 2 = 0%, P = 0.688) ( Fig. 2 f) and (I 2 = 42.376%, P = 0.188) ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations